Penerapan Program Kunjungan Rumah dalam Menumbuhkan Consciousness Siswa Terhadap Hukum pada Tata Tertib Sekolah di SMK Negeri 2 Tulungagung - Winda Anistiya Putri; Ajar Dirgantoro; Muhamad Abdul Roziq Asrori (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
The research aims to find out how the implementation of the home visit program and what are the inhibiting factors as well as supporting factors. This type of research is a qualitative descriptive method of collecting data observations, interviews, and documentation. The process of data analysis through data collection, data reduction, data presentation, and drawing conclusions. The results of the study are: (1) The application of a home visit program in growing awareness of the law on school rules is one of the activities that are very helpful for schools in dealing with problematic students, both in student behavior and in teaching and learning activities. (2) Implementation of a home visit program in growing awareness of the law in the code of conduct also has supporting factors and inhibiting factors. Supporting factors are the administration of correspondence or assignment letters that are complete and easy, and the time for student affairs is also easy for us to take home visits. While the inhibiting factors are very much the student's house which is far away, then the minimal transportation costs and the time when visiting the parents of students is not at home.